Frailty and falls in community-dwelling older adults in sub-Saharan Africa: A scoping review - Bertha Oppong-Yeboah; Nadjia Amini; Jannique van Uffelen; Evelien Gielen; Alfred Edwin Yawson; Jos Tournoy (Archives of Gerontology and Geriatrics Plus)
Purpose: Frailty and falls are two major health challenges in older adults, but little is known about their levels and interactions in community-dwelling older adults in sub-Saharan Africa. The purpose of this scoping review was to map the literature on frailty and falls with respect to their definitions, measurement methods, associated factors, and interactions in this setting. Methods: A systematic search of eight databases and four other relevant sources was performed with no language restriction using combinations of the keywords ‘frailty’, ‘older adults’, ‘falls’ and ‘Africa’ and their synonyms. Results: Thirty-six studies from nine countries in the sub-region met the inclusion criteria. The average age for participant inclusion in the studies was 50 years. The Frailty Phenotype and the Frailty Index were the primary assessment methods used, yielding frailty prevalence rates ranging from 5.4 % to 17.4 % and 20.6 % to 60.0 %, respectively. Fall prevalence ranged from 20.8 % to 55.1 %, while recurrent falls were reported in 11.0 % to 24.6 % of cases. Comorbidities/multimorbidity and increasing age were the most reported clinical and socio-demographic factors associated with frailty. Low functional status and being female were the primary factors associated with falls. Conclusions and recommendations: In sub-Saharan Africa, there appears to be a high prevalence of frailty and falls in a relatively young cohort of older adults. Future studies should focus on developing frailty definitions and assessment methods that are culturally appropriate in this setting.